Ochratoxin A production by Aspergillus niger: Effect of water activity and a biopreserver formulated with Lactobacillus plantarum CRL 778 - Gerez, Carla Luciana (2014)
Some filamentous fungi of the genera Aspergillus (A.) are of high impact in food safety due to the production of a toxic secondary metabolite, the ochratoxin A (OTA). The present study was carried out to evaluate the effect water activity (aw) on the growth and the OTA production by the strain Aspergillus niger 13D both invitro assays and in bread slices. High values of aw favoured growth and OTA production by A.niger 13D in Czapek Yeast extract agar medium (CYA) with the optimum at 0.995. In bread slices, fungi growth rate (μmax: 0.90-1.07cmd-1) and OTA production (5.13-10.79ngg-1) were lower respect to CYA medium (μmax: 1.09-1.81cmd-1, OTA concentration: 26.02-133.28ngg-1) independently to aw. Furthermore, efficacy antifungal of biopreserver formulated with Lactobacillus plantarum CRL 778 (SL778) for packed bread was evaluated. Our result evidenced the inhibitory activity of SL778 against growth of ochratoxigenic A.niger 13D in bread making at different aw. In addition, this biopreserver demonstrated is principally antimycotoxigenic, observing a reduction 60% of OTA at 0.995 and 0.971 aw in bread added with SL778.